Effect of Noni on Memory Impairment Induced by Hydrocortisone in Mice. (8th September 2022) - Zhang, Rui; Liu, Jinlian; Di, Songrui; Yu, Shuhui; Hou, Xinjuan; Zhao, Fan; Wang, Chandi; Zhu, Yingli; Tang, Ruying; Deng, Shixin; Wang, Chun; Zhang, Jianjun
Abstract : Background . Oxidative stress and memory impairment have been implicated as common functional brain diseases. Nuclear factor E2-related factor 2 (Nrf2) is highly induced in oxidative stress, indicating that Nrf2 is an emerging target of memory therapy. This study aimed to investigate the effect of noni on brain memory impairment induced by hydrocortisone and its protective mechanism in mice. Methods . Male Kunming mice ( n  = 8/group) were given hydrocortisone by gastric gavage for 14 consecutive days to establish the memory impairment model, except for those in the control group. On the same day, the corresponding drugs were given by gastric gavage. The changes in ethology were examined. The brains were extracted and subjected to western blot analysis and biochemical analyses to assess the activities of antioxidative stress. Results . The middle- and high-dose noni groups exhibited ameliorated ethology, and the high-dose noni group exhibited increased cerebral protein expression of Nrf2, Kelch-like ECH-associated protein 1 (KEAP1), and haem oxygenase-1 (HO-1) compared to the model group. The arrangement of CA3 vertebral cells in the hippocampus of mice was slightly compact, and hyperchromasia and pyknosis were alleviated. Furthermore, biochemical analyses showed that the activities of enzymes related to oxidative stress in the high-dose noni group were increased. Conclusions . Noni might be a powerful antioxidant that can protect nerve cells and may possess potential benefits for the treatment of memory impairment.